DEVELOPMENT OF WRIGHT BLENDING METHOD IN VISCOSITY ESTIMATION OF LIQUID-BINARY MIXTURE OF BASE OIL AND OLEFIN COPOLYMERS (OCPs) - Nelson Saksono; Subiyanto Subiyanto; Setyo Widodo (Scientific Contributions Oil and Gas, 2011)
This study aims to develop mathematical equations used in Wright’s method to predictkinematic viscosity of liquid-binary mixture consisting of base oil and additive. The equationis developed by addition of specific constants (αi and αc), representing interaction ofeach component in the mixtures. Evaluation is done using 70 empirical data from 35 samplesderived from liquid blending of 4 types of base oils (B.1, B.2, B.3 and B.4) and olefincopolymers (OCPs), varied in the range of 5-30 % of weight. Kinematic viscosity is measuredat 40oC and 100oC using a cannon automatic viscometer series 2000 (CAV 2000)according to ASTM method D 445. Validation of the equation (Developed-Wright’s method)is performed over all of liquid-binary mixtures of base oil-OCPs, and the accuracy isindicated by percent average absolute deviation (%AAD). The results show that the additionof specific constants could minimize the deviations of estimated values. The averagedeviation of Developed-Wright’s method on kinematic viscosity estimation at 40oC and100oC becomes 2.056 % and 1.917% respectively, lower than Wright’s method which are8.341 % and 14.696%; meanwhile the maximum deviation reaches 5.821 % and 4.657%,lower than Wright’s method which are 21.256 % and 25.265% respectively. These valuesindicate that the Developed-Wright’s method has better accuracy.